A randomised controlled trial of three psychological treatments for anorexia nervosa - Byrne, S.; Wade, T.; Hay, P.; Touyz, S.; Fairburn, C.; Treasure, J.; Schmidt, U.; McIntosh, V.; Allen, K.; Fursland, Anthea; Crosby, R. (Cambridge University Press, 2017)
Copyright © Cambridge University Press 2017 Background: There is a lack of evidence pointing to the efficacy of any specific psychotherapy for adults with anorexia nervosa (AN). The aim of this study was to compare three psychological treatments for AN: Specialist Supportive Clinical Management, Maudsley Model Anorexia Nervosa Treatment for Adults and Enhanced Cognitive Behavioural Therapy. Method: A multi-centre randomised controlled trial was conducted with outcomes assessed at pre-, mid- and post-treatment, and 6- and 12-month follow-up by researchers blind to treatment allocation. All analyses were intention-to-treat. One hundred and twenty individuals meeting diagnostic criteria for AN were recruited from outpatient treatment settings in three Australian cities and offered 25–40 sessions over a 10-month period. Primary outcomes were body mass index (BMI) and eating disorder psychopathology. Secondary outcomes included depression, anxiety, stress and psychosocial impairment. Results: Treatment was completed by 60% of participants and 52.5% of the total sample completed 12-month follow-up. Completion rates did not differ between treatments. There were no significant differences between treatments on continuous outcomes; all resulted in clinically significant improvements in BMI, eating disorder psychopathology, general psychopathology and psychosocial impairment that were maintained over follow-up. There were no significant differences between treatments with regard to the achievement of a healthy weight (mean = 50%) or remission (mean = 28.3%) at 12-month follow-up. Conclusion: The findings add to the evidence base for these three psychological treatments for adults with AN, but the results underscore the need for continued efforts to improve outpatient treatments for this disorder. Trial Registration: Australian New Zealand Clinical Trials Registry (ACTRN 12611000725965) http://www.anzctr.org.au/